2016
DOI: 10.3906/sag-1412-61
|View full text |Cite
|
Sign up to set email alerts
|

Posterior laminoforaminotomy in the treatment of lateralcervical herniated disc and foraminal stenosis

Abstract: Posterior laminoforaminotomy is applied to selected patients with a low complication rate. The advantages of this surgery are suitable visualization of the nerve root, preserved motion of the operated segment, avoidance of cervical instability, and a decrease in the length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…CLF and its' minimally invasive, microendoscopic, and microdiskectomy variants offer greater safety, major pros with few cons, and decreased costs vs. ACDF for patients with lateral/foraminal cervical disc disease and/or spondylosis [Table 1]. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CLF and its' minimally invasive, microendoscopic, and microdiskectomy variants offer greater safety, major pros with few cons, and decreased costs vs. ACDF for patients with lateral/foraminal cervical disc disease and/or spondylosis [Table 1]. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]…”
Section: Discussionmentioning
confidence: 99%
“…ree studies documented good/excellent postoperative outcomes with limited reports of adverse events following open CLF [Table 1]. [13][14][15] Yilmaz (2016) et al found that performing 83 open CLF to address posterolateral soft discs or foraminal stenosis resulted in 66 excellent and 13 good outcomes (Odom's Criteria); additionally, 79 (95%) showed improvement in postoperative radicular complaints, with just two adverse events (i.e., AE: 1 dural tear, and one wrong level surgery) [Table 1]. [13] Further pros for CLF included; better operative exposure to limit perioperative neural injuries, a shortened LOS, and greater preservation of stability (i.e., avoidance of fusion 1].…”
Section: Good/excellent Postoperative Outcomes With Limited Adverse E...mentioning
confidence: 99%
See 3 more Smart Citations